Computed tomographic angular measurements using a bone-centered three-dimensional coordinate system are accurate in a femoral torsional deformity model and precise in clinical canine patients - Brühschwein, Andreas; Schmitz, Bronson; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
Introduction In small animal orthopedics, angular measurements in the canine femur are often applied in clinical patients with bone deformities and especially in complex and severe cases. Computed tomography (CT) has been shown to be more precise and accurate than two-dimensional radiography, and several methods are described. Measurement techniques evaluated in normal bones must prove accuracy in deformed bones in clinical settings. Objectives The goals of our study were to evaluate the accuracy of canine femoral torsion angle measurements in a femoral torsional deformity model and to test repeatability and reproducibility of canine femoral neck inclination, torsion, and varus angle measurements in CT datasets of dogs applying a CT-based technique using a three-dimensional (3D) bone-centered coordinate system. Materials and methods For precision testing, femoral torsion, femoral neck inclination, and femoral varus angles were measured in CT data of 68 canine hind limbs by two operators, and their results were compared. For accuracy testing, a femoral torsional deformity model was preset from 0° to +/−90° with a goniometer and scanned. Torsion angles were measured in the CT data and compared to the preset value. Results In the femoral torsion model, the Bland–Altman plots demonstrated a mean difference of 2.11°, and the Passing–Bablok analysis demonstrated a correlation between goniometer and CT-based measurements. In the clinical CT scans, intra- and interobserver agreement resulted in coefficients of variation for repeated measurements (%) between 1.99 and 8.26 for the femoral torsion, between 0.59 and 4.47 for the femoral neck inclination, and between 1.06 and 5.15 for the femoral varus angles. Discussion Evaluation of femoral malformations with torsional deformities is the target area of this technique. Further studies are required to assess its value in different types, degrees, and combinations of osseous deformities and to establish normal reference values and guidelines for corrective osteotomies. Conclusion Based on the results of this study, the accuracy of the torsion angle measurements and the precision of inclination, torsion, and the varus angle measurements were considered acceptable for clinical application.